Economic development : principles, problems, and policies - Higgins, Benjamin Howard (New York : Norton, 1959)
This book is concerned with development problems of underdeveloped countries. It examines the rise of capitalism and the theories about it, the models of the principal classical economists, the stagnation theory of Hansen, and the Harrod growth model.
Includes bibliographical references and index.
lje 18/09/2018
Loans
Keywords: Economic development; Developing countries